(3GdebOeI GdCLQhejI aj Yde GdYQHjIs - (3GdUfgGLj, GHf BLQhe, CHh YHO Gddg, eMeO Hf YHO Gddg Hf OGhO, (B723 (3g`s ((3YKeGf GdaGge YHO GdQMefs)
(3ChdgG (B:s
(3bGd GdTjN GdEeGeCHh YHO Gddg eMeO Hf OGhhO GdUfgGLj YQa HGHf BLQhe GdcdGe aj GddZI jTed GdETGQI cbhd GdTGYQ CTGQJ HWQa GdYjf NajI CgdgG ETGQI hde JJcdes
(3BNQgG (B:s
(3aGdPj jJbOQ HGddGe agh bhdc ZdGe RjO hGdPj jJbOQ Hef fMh bhdc KhH NR Ch ef NR hHGH SGL Ch ef HGH SGL hNGJe MOjO heG CTHg Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 33s
(3eYLe GdeDdajf(B: 3 / 641s
(3cTa GdXfhf(B: 2 / 1796s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs